2015
DOI: 10.1039/c5ra15853b
|View full text |Cite
|
Sign up to set email alerts
|

Performance and mechanisms for removal of perfluorooctanoate (PFOA) from aqueous solution by activated carbon fiber

Abstract: 18 Sorption behaviors of perfluorooctanoate (PFOA) by activated carbon fiber (ACF) in 19 aqueous solution were investigated. The sorption of PFOA on ACF followed 20 pseudo-second-order kinetics and the sorption equilibrium reached at approximately 6 h. The 21 sorption of PFOA on ACF fitted the Freundlich model well. The sorption capacity of PFOA by 22 ACF decreased with the increasing pH, indicating that electrostatic attractive (pH < 7.4) and 23 repulsion (pH > 7.4) existed in the sorption process. Dissolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…A variety of results have been reported for the effect of pH on PFOA-sorption depending on the type of adsorbent. Sorption onto activated carbon fibres and single-walled carbon nanotubes (CNTs) decreased by 12 % and 32 %, respectively (Deng et al 2012;Wang et al 2015), when the pH was increased from 3 to 9 (attributed to increased repulsion), whereas sorption onto powdered activated carbon was relatively unaffected (Deng et al 2012), owing to a stable zeta potential in that pH range. A study comparing sorption of PFASs onto different types of CNTs found that pristine CNTs showed greater sorption compared with hydroxyl and carboxylfunctionalised CNTs (Deng et al 2012), which demonstrated the role of hydrophobic interactions in PFAS-sorption by carbonaceous adsorbents.…”
Section: Batch Sorption Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of results have been reported for the effect of pH on PFOA-sorption depending on the type of adsorbent. Sorption onto activated carbon fibres and single-walled carbon nanotubes (CNTs) decreased by 12 % and 32 %, respectively (Deng et al 2012;Wang et al 2015), when the pH was increased from 3 to 9 (attributed to increased repulsion), whereas sorption onto powdered activated carbon was relatively unaffected (Deng et al 2012), owing to a stable zeta potential in that pH range. A study comparing sorption of PFASs onto different types of CNTs found that pristine CNTs showed greater sorption compared with hydroxyl and carboxylfunctionalised CNTs (Deng et al 2012), which demonstrated the role of hydrophobic interactions in PFAS-sorption by carbonaceous adsorbents.…”
Section: Batch Sorption Studiesmentioning
confidence: 99%
“…As degradation of these chemicals is an energy-intensive process and presents challenges especially for use in situ, adsorption is a cost-effective strategy to manage PFOA contamination in situ by reducing contaminant mobility. Sorption of PFOA onto surfaces of carbonaceous materials (like chars, activated-C and nanotubes) (Deng et al 2012;Wang et al 2015) have been demonstrated, with granular activated-C used most commonly for the treatment of PFASs in ex situ filtration systems. These rely on hydrophobic interactions at the non-polar C-phase (Kucharzyk et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of PFOA sorption on active carbon fiber by OM was reported in a study where no obvious sorption occurred with increasing OM concentration to 500 mg L −1 ( Wang et al., 2015a ). These results support competitive sorption between OM and PFOA, and the pore blockage of active carbon fiber by OM.…”
Section: Mechanisms Of Contaminant Adsorption On Microplastics and Fa...mentioning
confidence: 74%
“…As indicated in Fig. 2 (a) ( Wang et al., 2015a ; Llorca et al., 2018 ), hydrophobic interaction between MPs and PFAS generally increased the adsorption affinity of MPs on longer-chain compounds. Although the effect of salinity should not be overlooked, adsorption of PFAS on PS in freshwater was higher than on PE and PVC.…”
Section: Mechanisms Of Contaminant Adsorption On Microplastics and Fa...mentioning
confidence: 74%
See 1 more Smart Citation